Glyphosate associado à competição com plantas daninhas e à aplicação de herbicidas em pré-emergência para a cultura da soja RR - Osipe, Jethro Barros (2012)
With the development of RR technology, applications of glyphosate on crops have become increasingly frequent. Two experiments were conducted in the agricultural year 2010/2011, in order to evaluate the effects of glyphosate applied post-emergence of soybean RR associated with competition by weeds and with applying of herbicides in pre-emergence. At first, the soybean crop had three types of management (with weed competition, application of glyphosate post-emergence, and both) in six different time periods. The results showed that independent of the time of application of post-emergence, there was a reduction in grain yield of soybean when glyphosate was used. Living with weeds damaged to the crop, causing losses of up to 67% in yield. The stress caused by competition with weeds not emphasized the negative effect of glyphosate on grain yield of soybeans. In the second experiment, the application of herbicides in pre-emergence was supplemented or not with glyphosate. All herbicides applied pre-emergence reduced the size of the soybean plants initially,however, generally they did not affect the yield of the crop. Only the herbicide flumetsulam at doses of 78 and 140 g ha-1, associated with post-emergence glyphosate, reduced the grain yield of soybean.